THE Strategies for Teaching Academic Vocabulary: Strategies for Teaching Academic Vocabulary - Jo’rayev, Muhammadrahimxon (Maktabgacha taʼlim jurnali, 2021)
Contemporary instructors use various efficient methods to teach several types of vocabulary. Most teachers make mistakes while introducing a new word by giving a lexical definition as a dictionary definition which is difficult to understand for them. In this article, there are several types of methods which teachers can implement them into education process.